Prosesi Upacara Perkawinan Tradisi Jawa Di Daerah Istimewa Yogyakarta - Saruda Widodo; Nyoman Santiawan (Pasupati, 2022)
Since ancient times, the Javanese people have had very complete traditional ceremonies in traditional wedding ceremonies. The marriage procession is divided into three stages, the first stage is pre-marriage, the second stage is during the marriage ceremony, and the third stage is after marriage. This study aims to determine the Javanese traditional marriage procession in the Special Region of Yogyakarta. This research is a qualitative descriptive study using data collection methods through library studies, observation and documentation. The results of the research are: 1. The procession of the event before the wedding, namely watching, applying, asak tukon, paningset and srah-srahan; 2. The procession at the time of marriage, namely the tarub and tawuhan ceremony, siraman ceremony, ngrik ceremony, midodareni ceremony, ijab ceremony, panggih ceremony, bridal pawiwahan and pahargyan (reception); 3. The procession after the wedding is bringing the bride and groom. The Javanese traditional marriage procession from the start of the application to the boyongan is full of educational values of noble character through the symbols of offerings or uborampe. Uborampe offerings in every procession of Javanese traditional wedding ceremonies have very noble meanings and values that must be understood and preserved, and we serve as guidance in carrying out traditional ceremonies inherited from our ancestors.